Learning path : software architecture fundamentals. - Ford, Neal; Richards, Mark; Safari eBooks ([Place of publication not identified] : O'Reilly Media, 2015)
"Being a software architect is more than just possessing technical knowledge. It's about thinking like an architect, being a leader, and understanding the architectural elements, patterns, and styles necessary to create effective software architectures. In this Learning Path, Neal Ford and Mark Richards empower you with the essential skills you need to be effective in this role."--Resource description page.
Software architecture fundamentals understanding the basics / Neal Ford & Mark Richards -- Software architecture fundamentals : taking a deeper dive / Neal Ford & Mark Richards.
Presenters, Neal Ford, Mark Richards.
Title and publication information from resource description page (Safari, viewed March 15, 2016).
Keywords: Software architecture; Electronic books